Suda az çözünen ilaçların siklodekstrin hidrojeller ile taşınımı - Bora, Nil (My University, 2006)
Siklodekstrinler (CD’ ler) inklüyzon kompleksi oluşturma yöntemiyle ilaçların istenmeyen özelliklerini azaltabilme yeteneğine sahiptir. Siklodekstrin içeren bir polimer siklodekstrinin inklüzyon kompleksi oluşturma özelliğini ve polimerlerin özelliklerinin her ikisini birleştirebilir. Bu çalışmada yeni bir -siklodekstrin (-CD) üretan metakrilat monomeri, -siklodekstrin ile toluen-2,4-diizosiyanat (TDI) ve 2-hidroksietil metakrilat (HEMA)’ ın reaksiyonları sonucu sentezlendi. -CD’ nın inklüzyon karakterine dayalı olarak, farklı kompozisyonlarda bir seri hidrojeller -siklodekstrin üretan metakrilat monomer, poli (etilen glikol) diakrilat (PEG-DA), HEMA ve fotobaşlatıcıdan oluşan karışımın oda sıcaklığında UV radyasyonu ile polimerizasyonu sağlandı. Hidrojellerin jel yüzdeleri ve kuru jellerin denge şişme değerleri (%) araştırıldı. İlaç adsorpsiyonu ve hidrojellerin kontrollü salınım davranışını araştırmak için metil oranj suda çözünür, rifampisin ise suda az çözünen ilaçları temsilen model ilaçlar olarak seçildiler. Metal oranj ve rifampisin salınımları (pH 7,4; 37 oC) sırasıyla 464 nm ve 474 nm’ de spektrofotometrik olarak saptandı ve ilaç salınım yüzdeleri karşılaştırıldı

Cyclodextrins (CDs) are capable of alleviating the undesirable properties of drug molecules in various routes of administration through the formation of inclusion complexes. A CD containing polymer can combine both the favorable property of CDs to form inclusion complexes and properties of polymers. In this study a new -cyclodextrin (-CD) urethane methacrylate monomer was synthesized from the reaction of toluene-2,4-diisocyanate (TDI) and 2-hydroxyethyl methacrylate (HEMA) with -cyclodextrin. Based on inclusion character of -CD, a series of hydrogels with different compositions were prepared by irradiating the mixtures of -cyclodextrin urethane methacrylate monomer, poly (ethylene glycol) diacrylate (PEG-DA), HEMA and photoinitator by UV radiation at ambient temperature. Gel percentage of the hydrogels and equilibrium swelling ratios (%) of dried hydrogels were investigated. Methyl orange and rifampicin were used as were soluble and sparingly soluble drug models, respectively for the investigation of drug adsorption and controlled release behaviours of the hydrogels. Methyl orange and rifampicin releases (pH 7,4; 37 oC) were determined spectrophotometrically at 464 nm and 474 nm, respectively and drug release percentages were compared.
Keywords: Biyokimya